2016
DOI: 10.1007/s00595-016-1433-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the preoperative peripheral lymphocyte count and lymphocyte percentage in patients with colorectal cancer

Abstract: These findings suggest that the lymphocyte percentage is a good predictor of the OS and may be a stronger predictor of survival than the lymphocyte count in CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
5
44
0
Order By: Relevance
“…As a basic component of cellular immunity, a low lymphocyte count might be responsible for a poor and insufficient immunologic reaction against tumor progression. Iseki et al [ 26 ] reported that patients with high peripheral lymphocyte count and percentage were likely to achieve a higher 5-year survival rate than those with low peripheral lymphocyte count and percentage. On the other hand, a decreased serum albumin level partially reflects a malnutritional status in the host and weak human systematic defense, and thus, might be associated with increased morbidity and mortality of cancer [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a basic component of cellular immunity, a low lymphocyte count might be responsible for a poor and insufficient immunologic reaction against tumor progression. Iseki et al [ 26 ] reported that patients with high peripheral lymphocyte count and percentage were likely to achieve a higher 5-year survival rate than those with low peripheral lymphocyte count and percentage. On the other hand, a decreased serum albumin level partially reflects a malnutritional status in the host and weak human systematic defense, and thus, might be associated with increased morbidity and mortality of cancer [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR would be a simple, inexpensive and reliable pretreatment prognostic factor for patients treated with TKIs. Iseki et al showed that LYM% was affected by neutrophils and monocytes, which is the reason why LYM% re ects systemic in ammation more accurately than absolute lymphocyte counts 24 . The results is consisted with our conclusion in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…That this number of traits and genes were identified with detectable regulation by epistasis is remarkable considering that only a single time point was examined, gene expression was only measured in the liver, and only one pairwise strain combination of CSSs was examined. Given that ly% and rdw are associated with diagnosis and prognosis in cancer patients as well as cardiometabolic disease, identifying a more complete genetic model that incorporates interaction may improve our ability to predict those at greatest risk or modulate these traits based on improved knowledge of the biological pathways that underlie these interactions (ISEKI et al 2017;ZHAO et al 2017;PILLING et al 2018).…”
Section: Discussionmentioning
confidence: 99%